Digital Leadership: Transforming Vocational High School into Regional Public Service Agency - Puspitaningsih, Arin Ika; 'Alam, Ghasa Faraasyatul; Burhanuddin, Burhanuddin; Imron, Ali; Sobri, Ahmad Yusuf; Purnomosari, Agustin (Angstrom Centre of Education, 2025)
The study aims to provide insights into the principal's role in transforming Vocational High School (VHS) management into a Regional Public Service Agency (RPSA) using digital tools. The study was conducted at SMKN 1 Banjarmasin, one of the VHS-RPSAs in Banjarmasin, South Kalimantan Province, as a descriptive qualitative research. The data was collected through interviews and document analysis. It was analyzed using qualitative techniques like data condensation, presentation, and conclusion drawing/verification assisted by NVivo. The study revealed that the principal transformed VHS management into RPSA using digital tools like video conferencing, presentation software, and online collaboration platforms for improved efficiency, transparency, and quality of educational services. It positively impacted VHS management, offering practical guidance for navigating the challenges of a digitalized education.